Mereduksi Noise Citra Ortokromatik Menggunakan Algoritma Weighted Mean Filter - Siagian, Edward Robinson (Building of Informatics, Technology and Science (BITS), 2020)
Digital camera recording images often have a number of disturbances that may occur, such as lens out of focus, spots appear due to imperfect capture, uneven lighting resulting in non-uniform intensity, image contrast is too low so objects are difficult to separate from background, or interference caused by dirt that adheres to the image and so forth. Noise is an image or pixel that interferes with image quality. Noise can be caused by physical (optical) interference with the acquisition tool or intentionally due to inappropriate processing. Examples are random or unwanted black or white spots that appear in the image. These random spots are called salt & pepper noise. By using the Weighted Mean Filter method, images that have noise can be overcome so that the resulting image can be better than the previous image.